Thermospira aquatica gen. nov., sp. nov., a novel thermophilic spirochete isolated from a Tunisian hot spring, and description of the novel family Thermospiraceae. Issue 1 (25th January 2023) - Gam, Zouhaier Ben Ali; Thioye, Abdoulaye; Cayol, Jean-Luc; Postec, Anne; Bartoli-Joseph, Manon; Vandecasteele, Céline; Erauso, Gaël; Labat, Marc
Abstract : A novel thermophilic, anaerobic bacterium, strain F1F22 T, was isolated from hot spring water collected in northern Tunisia. The cells were non-motile, Gram-negative and helical with hooked ends, 0.5×10–32 µm in size. Growth of the strain was observed at 45–70 °C (optimum, 55 °C), in 0.0–1.0 % (w/v) NaCl (optimum without NaCl) and at pH 6.5–8.5 (optimum, pH 7.5). Yeast extract was required for growth, and the strain grew on glucose, sucrose and maltose. The major fatty acids were C16:0 (40.2 %), iso-C16: 0 (30.2 %) and C16 :0 DMA (14.5 %). The genome consisted of a circular chromosome (2.5 Mb) containing 2672 predicted protein-encoding genes with a G+C content of 43.15 mol %. Based on a comparative 16S rRNA gene sequence analysis, strain F1F22 T formed a deeply branching lineage within the phylum Spirochaetota, class Spirochaetia, order Brevinematales, and had only low sequence similarity to other species of the phylum (lower than 83 %). Genome-based analysis of average nucleotide identity and digital DNA–DNA hybridization of strain F1F22 T with Treponema caldarium DSM 7334 T, Brevinema andersonii ATCC 43811 T and Spirochaeta thermophila DSM 6578 T showed values between 63.26 and 63.52 %, and between 20 and 25 %. Hence, we propose strain F1F22 T as a representative of a novel family ( Thermospiraceae fam. nov.), genus and species of Brevinematales : Thermospira aquatica gen. nov., sp. nov. (type strain F1F22 T =JCM 31314 T =DSM 101182 T ).